Improving Critical Thinking Skills in Digital Electronics Education Through Simulation-Based Learning Media, Taking into Account the Basic ICT Skills of Vocational High School Students - Nixson Jeheskial Meok; Ichsan Fahmi; Godlief Erwin Samuel Mige; Frans F. G. Ray (JTP - Jurnal Teknologi Pendidikan, 2026)
This study aims to analyze the effect of using simulation-based learning media on students’ critical thinking skills in digital electronics learning, with basic information and communication technology (ICT) skills as a moderator variable. This study employs a quantitative approach using a quasi-experimental nonequivalent control group design. The research subjects were 11th-grade students in the Industrial Electronics Vocational Program at SMK Negeri 2 Kupang, comprising an experimental group and a control group. Data analysis was conducted using a Two-Way Analysis of Variance (ANOVA). The results indicated a significant difference in critical thinking skills between students who participated in simulation-based learning and those who participated in conventional learning (p < 0.05). However, basic ICT proficiency did not show a significant effect on students’ critical thinking skills. Furthermore, no interaction was found between learning strategies and basic ICT proficiency regarding critical thinking skills. These findings indicate that the use of simulation-based learning media can be an effective strategy for enhancing students’ critical thinking skills in digital electronics courses at vocational high schools, regardless of their basic ICT proficiency.